2021
DOI: 10.3390/biom11010107
|View full text |Cite
|
Sign up to set email alerts
|

Renaissance of VDAC: New Insights on a Protein Family at the Interface between Mitochondria and Cytosol

Abstract: It has become impossible to review all the existing literature on Voltage-Dependent Anion selective Channel (VDAC) in a single article. A real Renaissance of studies brings this protein to the center of decisive knowledge both for cell physiology and therapeutic application. This review, after highlighting the similarities between the cellular context and the study methods of the solute carriers present in the inner membrane and VDAC in the outer membrane of the mitochondria, will focus on the isoforms of VDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 90 publications
(136 reference statements)
0
40
0
Order By: Relevance
“…In this perspective, VDACs are widely considered essential for the maintenance of the mitochondrial bioenergetic and the communication between the organelle and the rest of the cell (as reviewed in Shoshan-Barmatz et al, 2010 ; De Pinto, 2021 ).…”
Section: The Structure and Functions Of Vdac Proteinsmentioning
confidence: 99%
“…In this perspective, VDACs are widely considered essential for the maintenance of the mitochondrial bioenergetic and the communication between the organelle and the rest of the cell (as reviewed in Shoshan-Barmatz et al, 2010 ; De Pinto, 2021 ).…”
Section: The Structure and Functions Of Vdac Proteinsmentioning
confidence: 99%
“…Mitochondrial outer membranes contain large amounts of the mitochondrial porin termed the voltage-dependent anion channel (VDAC) [92,93]. When reconstituted into the artificial lipid bilayers, it forms ion channels that are phenotypically reminiscent of the maxi-anion channels: they have large conductance of app.…”
Section: Molecular Identity Of Maxi-cl: Rejected Candidatesmentioning
confidence: 99%
“…It is well known that the universal pathway for metabolite transport across the outer mitochondrial membrane is formed by the VDAC, which may be formed by different VDAC paralogs (e.g., [ 126 , 127 , 128 , 129 , 130 ]). The molecular mass cut-off for the transported molecules is assumed to be about 4 kDa although the limit could be decreased when VDAC switches to lower conducting substates featuring less anion selectivity [ 131 ].…”
Section: Non-proteinaceous Molecules Transported By Protein Import Channelsmentioning
confidence: 99%
“…Moreover, it has been observed that blocking the TOM complex with an imported protein decreased superoxide anion (O 2 •− ) release from mitochondria, particularly in the absence of functional yVDAC1 [ 135 ]. Notably, yeast mitochondria contain two VDAC paralogs (i.e., yVDAC1 and yVDAC2 [ 136 , 137 ]), both of which can form channels of comparable electrophysiological characteristics [ 130 ], but differ in their expression levels and (likely) substrate selectivity [ 138 ]. These postulated differences coincide with a yVDAC2 contribution to the global permeability of the mitochondrial outer membrane that has remained undetected to date [ 4 , 139 ].…”
Section: Non-proteinaceous Molecules Transported By Protein Import Channelsmentioning
confidence: 99%